Fast synthesis of copper nanoclusters through the use of hydrogen peroxide additive and their application for the fluorescence detection of Hg2+ in water samples. (7th May 2015) - Xiaoqing, Liao; Ruiyi, Li; Zaijun, Li; Xiulan, Sun; Zhouping, Wang; Junkang, Liu
Abstract : The study reported a fast synthesis of CuNCs through the use of hydrogen peroxide additive. The resulting CuNCs exhibit excellent fluorescence intensity and optical stability. Abstract : Copper nanoclusters (CuNCs) have become promising nanomaterials due to their high electronic conductivity and low cost. This study reports the fast synthesis of CuNCs through the use of hydrogen peroxide (H2 O2 ) additive and their application for the fluorescent detection of Hg 2+ in water samples. Cu 2+ was rapidly reduced into Cu 0 in the presence of H2 O2 and bovine serum albumin (BSA), further leading to the production of CuNCs. Under optimized conditions, the synthesis needs 1 h to achieve a high conversion rate of Cu 2+ (more than 99%). In the resulting CuNCs, no Cu 2+ can be found by the sodium sulfide test. Research on resonance light scattering, synchronous fluorescence and circular dichroism spectroscopy reveals that H2 O2 may play two important roles in the synthesis of CuNCs. One role as a ligand is to combine with BSA–Cu complex to form BSA–Cu–H2 O2 complex, which diminishes the reduction potential of Cu 2+ and leads to the fast reduction of Cu 2+ into Cu 0 . Another role as an oxidizing agent is to partly destroy disulfide bonds in BSA, which increases the degree of exposure of free amino groups. This results in an enhanced reduction ability of BSA towards Cu 2+ . Interestingly, the as-prepared CuNCs display better fluorescence intensity and optical stability when compared with the CuNCs prepared by the conventional method. The nanosensor based on the CuNCs was developed for the rapid, reliable, sensitive and selective sensing of Hg 2+ with a detection limit of 4.7 × 10 −12 M (S/N = 3) and a dynamic range of 1 × 10 −5 −1 × 10 −11 M. It has been successfully used for the detection of Hg 2+ in water samples.